THE USE OF THE ALGORITHM EVALUATION OF TECHNOLOGICAL COMPLEXITY OF CASTINGS TO ACCELERATE THE QUALITY OF THE VERIFICATION PROCESS OF GATING SYSTEMS DESIGNING - I. B. Odarchenko; V. A. Zharanov (Литьë и металлургия)
The parameters were selected and the analysis of their compliance to assess the processing complexity of castings was made. A variant of the organization of process design for the castings of varying difficulty, defined on a set of proposed geometrical parameters was proposed.